Edukasi Logging dan Interprestasi Data Sumur Sebagai Upaya Peningkatan Kompetensi Vokasi di SMK Migas Inovasi Pekanbaru - Richa Melysa; Novrianti Novrianti; Idham Khalid (PELANTAR PRESS, 2026)
The oil and gas industry requires high technical competence, especially in the field of formation evaluation. However, many vocational students face challenges in visualizing subsurface data due to limited access to specialized software and industrial equipment. This community service program aims to enhance the competency of students at SMK Migas Inovasi Pekanbaru through training in well logging and data interpretation. The method used includes technical socialization, hands-on workshops on reading log curves (gamma ray, resistivity and porosity), and evaluation through pre-tests and post-tests. The results showed a significant increase in students understanding with average scores rising from 45% to 82%. This activity successfully bridged the gap between school theory and industrial practice, preparing students for the workforce or higher education in the energy sector